2015
DOI: 10.1039/c5ra01254f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized γ-lactones via a three-component cascade reaction catalyzed by consecutive N-heterocyclic carbene systems

Abstract: Two consecutive N-heterocyclic carbene (NHC) catalytic systems were combined in a one-pot cascade reaction for the assembly of aromatic aldehydes and 2-haloenals into a structurally complex g-lactone backbone. To our knowledge, this is the first report of NHCcatalyzed [3 + 2] annulation of a,b-unsaturated acylazoliums with 1,2-bisnucleophiles.Scheme 1 Annulation based on NHC-catalyzed generation of a,b-unsaturated acylazoliums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In 2015, Huang reported a novel three-component coupling (see Scheme ). In this reaction, it is proposed that benzaldehyde ( 87 ) is dimerized via a benzoin reaction mediated by triazolylidene NHC B8 to give benzil 88 . Subsequent addition of α-bromoenal 44 and imidazolium precatalyst C1·HCl leads to the formation of the α,β-unsaturated acyl azolium intermediate 13 , which reacts with the enol form of benzil 88 .…”
Section: Cascades Involving Bond Formation At the β- And Acyl Carbonsmentioning
confidence: 99%
“…In 2015, Huang reported a novel three-component coupling (see Scheme ). In this reaction, it is proposed that benzaldehyde ( 87 ) is dimerized via a benzoin reaction mediated by triazolylidene NHC B8 to give benzil 88 . Subsequent addition of α-bromoenal 44 and imidazolium precatalyst C1·HCl leads to the formation of the α,β-unsaturated acyl azolium intermediate 13 , which reacts with the enol form of benzil 88 .…”
Section: Cascades Involving Bond Formation At the β- And Acyl Carbonsmentioning
confidence: 99%
“…Zhao et al . reported two consecutive NHC catalytic systems ( L119–L122 ) and ( L123 and L124 ) combined in a one‐pot cascade reaction for the assembly of 2‐haloenals ( 157 ) and aromatic aldehydes ( 156 ) into a structurally complex γ‐lactone backbone ( 158 ) providing 10–64% yields as shown in Scheme . Authors described the first report of NHC‐catalyzed [3 + 2] annulation of α,β‐unsaturated acylazoliums with 1,2‐bisnucleophiles and trying to clarify the detailed reaction mechanism and explore whether this approach can be applied to asymmetric domino reactions.…”
Section: N‐heterocyclic Carbenes As Ligands and Their Metal Complexesmentioning
confidence: 99%
“…Delany et al [201] reported the use of novel NHC ligands (L127-L134) bearing a bulky yet highly electrondeficient N-aryl substituent for the first highly chemoselective intermolecular benzoin condensations between two nonidentical aromatic aldehydes (179)(180) yielding benzoins (181)…”
Section: April 2019mentioning
confidence: 99%
“…134-135 °C. R f = 0.2 ( petroleum ether/ethyl acetate 5 : 1); [α] 25 D = 21 (c = 0.1, CH 2 Cl 2 ); HPLC analysis: 95% ee [Daicel CHIRALPAK IA column, 20 °C, 254 nm, hexane/ i-PrOH = 80 : 20, 1.0 mL min −1 , 254 nm, 17.1 min (minor), 48.1 min (major)]; 1 H NMR (400 MHz, CDCl 3 ) δ 7.43 (d, J = 8.9 Hz, 2H), 7.24-7.11 (m,3H),3H),4.75 (dd,J = 8.8,2.0 Hz,1H),2H), 3.83 (s, 3H), 3.10 (dd, J = 16.7, 8.8 Hz, 1H), 2.80 (dd, J = 16.7, 2.1 Hz, 1H), 2.44 (s, 3H), 1.26 (t, J = 7.1 Hz, 3H). 13 C NMR (100 MHz, CDCl 3 ) δ 164.…”
Section: General Experimental Detailsmentioning
confidence: 99%